2019
DOI: 10.1002/hed.25718
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline‐regulated ataxia telangiectasia mutated expression level in oral cancer progression

Abstract: Background Ataxia telangiectasia mutated (ATM) regulates DNA repair and cell cycle. The present study analyzed arecoline‐induced ATM expression during oral cancer progression. Methods In vitro studies were performed using oral squamous cell carcinoma (OSCC) cell lines treated with arecoline to analyze cell response and ATM regulation. in vivo studies were performed using immunohistochemistry to detect ATM expression in normal, oral potentially malignant disorder (OPMD), and OSCC tissues. Results Low‐dose areco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
(51 reference statements)
3
23
0
Order By: Relevance
“…Arecoline is an alkaloid extracted from betel nut and plays an essential role in the progression of oral cancer (101,102). Chang et al (38) treated C57BL/6JNarl mice with arecoline, 4NQO, or both arecoline and 4NQO for 8 weeks to induce oral carcinogenesis.…”
Section: Nqo Combined With Other Chemical Carcinogens 4nqo and Arecomentioning
confidence: 99%
“…Arecoline is an alkaloid extracted from betel nut and plays an essential role in the progression of oral cancer (101,102). Chang et al (38) treated C57BL/6JNarl mice with arecoline, 4NQO, or both arecoline and 4NQO for 8 weeks to induce oral carcinogenesis.…”
Section: Nqo Combined With Other Chemical Carcinogens 4nqo and Arecomentioning
confidence: 99%
“…The results showed that arecoline was able to inhibit ATM promoter activity in a dose-dependent manner ( Figure 1 E). Tu et al and our unpublished data also showed that arecoline could decrease ATM promoter activity in SAS, OEC-M1 [ 32 ], and KB cells (data not shown). These results indicate that ANE and arecoline suppress the expression of ATM and BRCA1 in hGFs and cancer cells.…”
Section: Resultsmentioning
confidence: 63%
“…Previously, we have reported an association between low ATM expression and poor patient outcome in laryngeal and pharyngeal cancers [ 8 ]. Yu et al also found that low ATM expression was correlated with a worse OS in oral cancer [ 32 ]. The HNC patients both in Yu et al’s and our studies have a habit of chewing betel quid (BQ), which ingredients may suppress the expression of ATM and BRCA1 [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arecoline is the major compound in betel nut that initiates the OSF process [ 41 , 42 , 43 ]. Low doses of arecoline enhance the cell proliferation rate, while high doses of arecoline induce total reactive oxygen species (ROS), DNA damage, and LOX activity [ 44 ]. The ataxia-telangiectasia mutated activated DNA repair is also inhibited by arecoline [ 45 ].…”
Section: Epidemiology Of Osfmentioning
confidence: 99%